What to eat now : the indispensable guide to good food, how to find it, and why it matters - Nestle, Marion (North Point Press / Farrar, Straus and Giroux, 2025)
"An updated classic on nutrition and food, Marion Nestle's What to Eat Now is a straightforward and comprehensive guide to cutting through the marketing and half truths in order to make healthy, delicious, and sustainable food choices at the grocery store"-- Provided by publisher.